Study of the rheological properties of the plasticizer to obtain a coal-water slurry - Tanasheva, N.K.; Minkov, L.L.; Tleubergenova, A.Zh.; Sadenova, K.K. (KU publ., 2019)
The article presents the results of the study of the impact of plasticizers on the stability of coalwater suspensions obtained from Shubarkul coal slurries. As part of the task to determine the optimal reagent-plasticizer, an experimental installationwas developed. Fuel oil, gelatin, sodium humate were used as reagents-plasticizers. The process of enrichment of coal slurries of Shubarkul Deposit was studied; it is shown that the best results are obtained with the use of sodium humate. The use of sodium humate as a plasticizer makes it possible to create coal-water suspensions with a spatial network-like structure that do not delaminate for a long time.
Сулы-көмірлі суспензия алу үшін пластификатордың реологиялық қасиеттерін зерттеу.
Исследование реологических свойств пластификатора для получения водоугольной суспензии.
Keywords: electro-hydro-impulse installation; Shubarkul coal; coal-water fuel; plasticizer reagent; ultrasonic dispersant